X-ray spectropolarimetry of the bright atoll Serpens X-1 - Ursini, F.; Gnarini, A.; Bianchi, S.; Bobrikova, A.; Capitanio, F.; Cocchi, M.; Fabiani, S.; Farinelli, R.; Kaaret, P.; Matt, G.; Ng, M.; Poutanen, J.; et al. (EDP Sciences, 2025)
We present simultaneous X-ray polarimetric and spectral observations of the bright atoll source Ser X-1 carried out with the Imaging X-ray Polarimetry Explorer (IXPE), NICER, and NuSTAR. We obtain an upper limit of 2% (99% confidence level) on the polarization degree in the 2 8 keV energy band. We detect four type-I X-ray bursts, two of which during the IXPE observation. This is the first time that has IXPE observed type-I X-ray bursts, and it allows us to place an upper limit on their polarization degree; however, due to the limited total number of counts in each burst, we obtain a relatively high upper limit (80%). We confirm the presence of reflection features in the X-ray spectrum, notably a broad iron line. Fitting the data with a relativistic reflection model, we derive a disk inclination of 25. The spectral and polarization properties are comparable with other atolls observed by IXPE, suggesting a similar accretion geometry, and the relatively low polarization is consistent with the low inclination.